2010
DOI: 10.1101/lm.1974510
|View full text |Cite
|
Sign up to set email alerts
|

‘Silent’ priming of translation-dependent LTP by β-adrenergic receptors involves phosphorylation and recruitment of AMPA receptors

Abstract: The capacity for long-term changes in synaptic efficacy can be altered by prior synaptic activity, a process known as "metaplasticity." Activation of receptors for modulatory neurotransmitters can trigger downstream signaling cascades that persist beyond initial receptor activation and may thus have metaplastic effects. Because activation of b-adrenergic receptors (b-ARs) strongly enhances the induction of long-term potentiation (LTP) in the hippocampal CA1 region, we examined whether activation of these recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 65 publications
(92 reference statements)
7
71
2
1
Order By: Relevance
“…1B; mean fEPSP slope was 142% + 7% 120 min after HFS). In a previous study (Tenorio et al 2010), a 1-h time lag between washout of ISO and HFS was used successfully to elicit metaplastic enhancement of LTP maintenance similar to our present study. Thus, acute bath application of NE can prime synapses to boost subsequent expression of long-lasting LTP.…”
Section: Norepinephrine (Ne) Induces Metaplasticity Of Ltpsupporting
confidence: 62%
See 3 more Smart Citations
“…1B; mean fEPSP slope was 142% + 7% 120 min after HFS). In a previous study (Tenorio et al 2010), a 1-h time lag between washout of ISO and HFS was used successfully to elicit metaplastic enhancement of LTP maintenance similar to our present study. Thus, acute bath application of NE can prime synapses to boost subsequent expression of long-lasting LTP.…”
Section: Norepinephrine (Ne) Induces Metaplasticity Of Ltpsupporting
confidence: 62%
“…Also, NE paired with high-frequency stimulation (HFS) enhanced field EPSP (fEPSP) potentiation in CA1 of rat hippocampal slices (Katsuki et al 1997). Additionally, Tenorio et al (2010) found that ISO enhanced future LTP through a process known as "metaplasticity" (see Abraham and Bear 1996).…”
Section: Norepinephrine (Ne) Induces Metaplasticity Of Ltpmentioning
confidence: 99%
See 2 more Smart Citations
“…Rat cortical neurons were treated with NMDA or glycine, chemical stimuli shown to induce LTD or LTP, respectively (cLTD/cLTP), and which are known to regulate S845 phosphorylation (26)(27)(28). Alternatively, neurons were treated with Iso, a noradrenaline analog known to result in phosphorylation of GluA1 S845 via activation of β-adrenergic receptors and PKA (10,17,23,29,30). cLTD treatment significantly reduced the levels of phospho-S845, whereas cLTP and Iso increased the signal of phospho-S845 (Fig.…”
Section: Quantification Of Phospho-glua1 Containing Ampar Tetramers Umentioning
confidence: 99%